Advancing Teacher Performance through Learning Innovation in the Age of Artificial Intelligence: A PRISMA-Based Systematic Literature Review - Lisa Chandrasari Desianti; Siti Hasanah (AGUSPATI Research Institute, 2026)
This review synthesizes research on teaching methods or strategies that enhance critical thinking in students to address variability in pedagogical effectiveness and assessment across educational contexts. The review aimed to evaluate the impact of diverse instructional approaches on critical thinking development, identify methodological trends, and analyze challenges in implementation. A systematic selection of empirical studies and meta-analyses spanning elementary to higher education, multiple disciplines, and global settings was conducted, emphasizing quasi-experimental and mixed-method designs. Findings indicate that project-based and inquiry-based learning consistently improve critical thinking by engaging students in authentic problem-solving, particularly when integrated with STEM and digital technologies. Technology-enhanced pedagogies, including AI tools and blended learning, further support critical thinking but face barriers related to access and teacher preparedness. Assessment practices vary widely, with continuous and formative evaluations proving more effective than isolated tests, though standardization remains limited. Additionally, professional development for educators is critical to sustain effective critical thinking instruction, while interdisciplinary and collaborative strategies foster integrative cognitive skills despite coordination challenges. These findings converge to underscore the necessity of comprehensive, technology-supported, and teacher-facilitated frameworks for cultivating critical thinking. The review highlights implications for designing scalable, context-sensitive pedagogies and calls for rigorous longitudinal research to validate sustained outcomes.